2018
DOI: 10.1680/jcoma.16.00076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on self-compacting concrete reinforced with different chopped fibers

Abstract: The development of self-compacting concrete (SCC) is a revolutionary landmark in the history of the construction industry. Incorporation of fibres further enhances the properties, especially those related to the post-crack behaviour of SCC. The fibres used in the study are 12 mm long chopped glass fibre, carbon fibre and basalt fibre. The volume fractions of fibre taken are 0·0, 0·1, 0·15, 0·2, 0·25 and 0·3%. The research comprised two stages: the first stage consisted of the development of an SCC mix design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The properties of the hardened concrete (toughness, impact resistance, etc.) will foreseeably be improved by the addition of fibers (Jena et al, 2018), although the behavior in the fresh state will, in general, worsen. 2017) used only coarse RCA.…”
Section: Fresh State Of Scc With Rca and Fibersmentioning
confidence: 99%
“…The properties of the hardened concrete (toughness, impact resistance, etc.) will foreseeably be improved by the addition of fibers (Jena et al, 2018), although the behavior in the fresh state will, in general, worsen. 2017) used only coarse RCA.…”
Section: Fresh State Of Scc With Rca and Fibersmentioning
confidence: 99%
“…Zhang et al 22 stated that compressive strength decreased by 4.1% when 0.30% BF content was used in the concrete mixture. Jena et al 23 in their studies investigating the effect of GF on SCC, they concluded that the adding of GF to SCC by 0.30% by volume decreased compressive strength by 4.30%. Komlos et al 24 reported that PPFs have no obvious impact on the compressive strength of concrete.…”
Section: Resultsmentioning
confidence: 99%
“…[6]. The use of silica fume allowed for the investigation of the effect that a variety of chopped fibers would have on the characteristics of self-consolidating concrete [7]. Following the rapid chloride migration test, a model was constructed to explain how chlorine made its way into marine concrete [8].…”
Section: Introductionmentioning
confidence: 99%